PENGUSIRAN MASSAL PENGUNGSI AFRIKA UTARA DARI JERMAN DAN PERMASALAHANNYA - Gibson Radityo; Ida Kurnia (Jurnal Hukum Adigama, 2018)
United Nation High Commissioner of Refugee (UNHCR)  is an internasional organization made under United Nations (UN) specifically for asylum seeker and refugee issues. As an international organization, UNHCR have a legal personality which is give them power to do such a legal action, yet from that power make UNHCR also gets its rights and respondsibility. According to UNHCR statute, Vienna Convention 1951 and Protocol 1967, one of UNHCR respondsibility is to protect and keep the refugee safe and make sure the third parties nation do all the responsibility to keep and protect the refugee. But how, if there is an issue that a nation break the international convention for refugee by force the refugee back to their home, yet the refugees already proved to do crimes againts the third parties nation policy? yet if the refugees forced  back to their origin couuntry, they will be threathened, so how suppose the UNHCR as an international organization for refugee do according to the UNHCR statute and Convention of refugees?in that case it will give a responsibility for UNHCR to solve the issue for the refugee. As the case above, the author have an insterest to summarizes the issue as my thesis.